Application of root cause analysis as a tool in hospital security management - Novaretti, Marcia Cristina Zago (Revista de Administração da UFSM, 2014)
Errors may occur in any institution, involving any professional and, in most of the cases, are preventable. The objective of this case study is to demonstrate that errors can be minimized when analyzed by an interdisciplinary team. Root cause analysis (RCA) was used in 49 events related to medication errors and canceled surgeries occurred in 2013 in a public hospital. We implemented 29 corrective actions, 30 work routines, reduced in 29% the notification number of surgery undertaken and zero out the notification regarding failure packaging. The RCA works in an interdisciplinary way includes people who hold knowledge about the processes involved in error events and people with different levels of experience and training. This study focuses on systems and work processes and not on individual performance. The RCA characteristic is to ask what, why and how the fact happened. It is recognized that the RCA methodology has limitations, but the benefits that can be derived from it due to its critical thinking concerning each incident and the implementation of corrective actions, as well as its preventive and not punitive character, outweigh its weaknesses. Therefore, the suggestion is to use it to minimize the risks of an institution.